The Influence Of Youth Empowerment Through Development Of Rafting Tourism Business Entity Village Owned to Youth Capacity Buluh Duri Village Sipispis Subdistrict - Wahyudi Rambe; Badaruddin; Lita Sri Andayani (International Journal of Science, Technology & Management, 2021)
The presence of Law No. 6 of 2014 on Villages, has brought new hope for the birth of efforts to increase the capacity of the community of BuluhDuri Village, including for. Efforts to increase the capacity of the youth of Buluh Duri Village are carried out by the Village Owned Enterprises (BUMDes) Buluh Duri Mandiri (BUDUMA) through the development of Rafting TourismUnit. This research was conducted to find out the influence of empowerment consisting of enabling, empowering, andprotecting the capacity of the youth of Buluh Duri Village in the development of BUMDes BUDUMA Rafting Tourism Unit. This research was conducted with quantitative approach through a survey on a sample of 38 respondents. Data analysis is performed using multiple linear regression tests. The results of the partial analysis using the T test showed that the three independent variables tested, namely enabling, empowering, and protecting had a positive and significant influence on the variable capacity of the youth of Buluh Duri Village. The results of the analysis conducted simultaneously using the F test showed independent variables consisting of enabling, empowering, and protecting simultaneously significantly affect dependent variables, namely capacity in the youth of Buluh Duri Village.